Comparison Between Treated and Untreated Zeolite Towards the Performance of Polyethersulfone Mixed Matrix Membranes (MMMs) for O2/N2 Gas Separation - Norida, Ridzuan; Muhammad Hidayat, Musa (Trans Tech Publication, 2012)

(untitled)
Mixed Matrix Membranes (MMMs) is one of the alternative ways to increase the performance of plain polymeric membrane. In this study, the performance of MMMs using treated zeolite and the ones using untreated zeolite were compared to see the effect of the coupling agent towards the separation of O2 and N2. The polymer solution contains Polyethersulfone (PES) as the polymer, N-Methyl Pyrrolidone (NMP) as the solvent and distilled water (H2O) as the non-solvent. For the MMMs using treated zeolite, the zeolite was first treated using Aminopropyl- Trimethoxysilane (APTMOS), a silane coupling agent before inserted into the polymer solution. For both types of MMMs, the zeolite concentration between 5 to 20 wt % were applied. The dry/wet phase inversion methods were used to produce the asymmetric flat sheet membrane. The prepared membranes were coated with silicone and N-Hexane in order to decrease the surface defect of the membrane. The best performance had found for membranes using treated zeolite where the selectivity was 3.3 for 15 % zeolite concentration at 3 bar operating pressure compare to the untreated zeolite . As a conclusion, it believe that surface modification of zeolite plays an important role to the incompatibility of zeolite and polymer to the formation of large free voids and it affected the overall selectivity and permeability.